Market Sensing Today - Prince, Melvin; Priporas, Constantinos-Vasilios (Business Expert Press, 2015)
Today's practicing marketers and scholars are confronted with a wide array of conflicting and imprecise information about best practices by which to search, gather, consolidate and interpret market information. Consequently, the need has never been greater to optimize market sensing to generate managerial actions that efficiently and effectively utilize knowledge of emerging consumer needs and competitive threats. This book addresses these urgent concerns. In essence, Market Sensing Today will cover, in ground-breaking ways, the following marketing managerial areas: * marketing opportunities associated with conventional and progressive bases of segmentation. * trends in market segment size and growth affecting long-range planning. * strategic direction for reaching future goals. * managerial understanding of assumptions competitors make about themselves. * the direction of current market strategies. * adding to the knowledge of a firm's core competencies. * how new market knowledge is best integrated into a firm's market intelligence system. * best ways to ensure the quality of information underlying decisions. * how benchmarking improves with market sensing. * best approaches for translating business issues into projects. * ways that key information may be disseminated within firms. * how proposed strategic changes are promoted by market sensing. * roles customer satisfaction insights play in policy. This book will address these key issues and more, to advance theory, research and practice based on latest developments in this vital field. It will show how to re-formulate traditional models that no longer work.
Keywords: dept.mrk; faculty_collection

Effect of stress, materialism and external stimuli on online impulse buying - Moran, Brittanie (Journal of Research for Consumers, 2015)
Keywords: dept.mrk

Continuties in Market Sensing - Prince, Melvin; Priporas, Constantinos-Vasilios (Market Sensing Today, 2015)
The concept and framework of market sensing was introduced by George Day more than 20 years ago into the strategic marketing literature and especially the philosophy of the market-driven organization. Market sensing can be considered an expression of a company's capabilities to scan the external environment. It does this by using real time data and intelligence to understand business or uncertain changes, to meet the current and future needs of the market, increase customer value, and outperform competitors. Market sensing enables managers to resist complacency, as well as to exploit opportunities and to design appropriate competitive strategies in order to remain successful in today's uncertain, rapidly changing, and hypercompetitive market. The present volume, Market Sensing Today, is essential reading in the marketing discipline, given the rapidly escalating innovative developments in market sensing techniques. This book of essays by acknowledged experts in the field fills an important knowledge gap and provides a realistic basis for strategy. It is replete with real-life examples of market sensing that illustrate actionable ideas for immediate impact that will improve organizational learning and accelerate growth. This book of contemporary tested and comprehensive concepts and methods grounded in diverse and rich experience is intended to stimulate creativity and insightful approaches for educators offering courses in strategy as well as for practitioners involved in crucial strategic decision making.
Keywords: Business & Economics / Marketing / General; Marketing research; dept.mkt; faculty_collection

Dependence and interdependence in marketing relationships: meta-analytic insights - Scheer, Lisa K.; Miao, C. Fred; Palmatier, Robert W. (Journal of the Academy of Marketing Science, 2015)
The authors conduct a meta-analysis to examine dependence and interdependence in marketing relationships. Analyses reveal that dependence affects performance primarily through relationship quality and cooperation, while interdependence has substantial direct effects as well as effects mediated through relationship-specific investments and cooperation. Regarding relationship context, effects of dependence are stronger in channel relationships than end-user relationships and for services than goods; interdependence does not display the same pattern. Regarding methodological context, dependence measures that emphasize relationship value versus switching costs have different moderating effects; greater general dependence content is associated with weaker effect sizes for dependence but conversely greater effect sizes for interdependence. These results suggest that new insights can be gained by distinguishing relationship value and switching cost components of dependence and by investigating the possibility that the conceptual domain of interdependence differs from that of dependence. Future research that strives for greater precision in the measurement of dependence and interdependence constructs and that simultaneously examines dependence and interdependence is recommended.
83 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/051-075-141-803-787 tex.eissn: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Channels; Dependence; Interdependence; Measurement; Meta-analysis; Relationship value dependence; Relationships; Switching cost dependence; dept.mkt

Knowledge and skills transfer between MBA and workplace - Prince, Melvin; Burns, David J; Lu, Xinyi; Winsor, Robert D (Journal of Workplace Learning, 2015)
Purpose-This paper aims to use goal-setting theory to explain the transfer of knowledge and skills between master of business administration (MBA) and the workplace. Design/methodology/approach-Data were obtained by an online survey of MBA students enrolled in at four US graduate business schools. These were a public and private institution in the Northeast region, a private sectarian institution in the Midwest region and a private institution in the Pacific region. All students worked while attending the university. The sampling frame consisted of each school’s MBA enrollees. Questionnaires were distributed to a random cross-section of part-time students at each graduate school of business representative of returned by 144 students. The profiles of responders were consistent with parameters for the entire MBA student population. Findings-The research shows that multiple goals of reciprocal knowledge and skills transfer may be in harmony and mutually reinforcing. In principle, each goal is more likely to be attained with greater economy of effort than might be surmised. Additionally, the same forces may act similarly to facilitate attainment of two well-integrated goals, in this case transfer betweenMBAstudies and work, as well as between work and MBA studies. Research limitations/implications-The present study involved participants from part-time public and private MBA granting institutions in the USA. The study tested and extended goal-setting theory and introduced the innovative concept of reciprocal transfer. Future studies should seek to generalize the findings to a broader population of part-time MBA students, especially from other nations. Despite its strengths, the findings of this study need to be interpreted in the perspective of some limitations. The current study did not measure transfer climates in either the organization or university settings. Transfer climates undoubtedly have an important bearing on transfer outcomes. Practical implications-Review of the present study suggests that a positive MBA environment is needed to influence motivation to learn and perceptions of the MBA program’s utility, thereby promoting transfer of knowledge and skills to MBA studies from the workplace. A supportive work-to-MBA-studies transfer climate will lead to more active learning of course content that has greater relevance for achieving career goals. Potentially generalizable from the organizational transfer climate literature (Rouiller and Goldstein 1990; Rouiller and Goldstein 1993), positive transfer from work to MBA studies will occur when appropriate situational cues and consequences are present in the program. Social implications-A constructive implication suggested by the findings of this study would be the intervention and transfer management by educators to structure and strengthen the university transfer climate of their part-time MBA programs. Traditionally, the concept of transfer climate has been primarily applied to employee workplace training activity and job performance. The university culture of the MBA student might emphasize and reward continuous learning from workplace experiences. Opportunities at the university should be provided for the exercise of newly acquired workplace skills that reinforce MBA learning experiences. Originality/value-This is the first study that shows how learning goals and performance goals are integrated in the context of a new concept, i.e. reciprocal transfer of knowledge and skills betweenMBA and workplace settings. It also demonstrates, for the first time, the impact of learning and motivation for MBAstudies and perceived utility ofMBAprogram on the extent of transfer of learning and skills from the workplace to the university setting. © Emerald Group Publishing Limited.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/131-480-418-077-781 tex.type: [object Object]
Keywords: Knowledge transfer; Learning orientation; Management education; Performance; dept.mkt